Estandarización de un proceso productivo para la elaboración de vinos a base de desechos frutales - Paucar Gualotuña, Katerine Stefanía (2019)
In this research work, a study was carried out on the winemaking process in order to optimise the fruits rejected in the commercial premises, which are discarded weekly between 11.11% and 30% with different fruits. A documentary study of the most commonly used methods for wine production was carried out, and the most appropriate method was justified, taking into account the technological process, the conditions of the commercial premises and their productivity. Theoretical foundations of standardization and strategies were for analyzed the fermentation processes, the bibliographic and field study will determine the efficiency of the process for the elaboration of wine and the use of the fruit residues in the current circumstances. Its goal is to propose a guide for the standardization of the winemaking process by the semi-industrial artisanal method from the reuse of fruit waste. The guide was prepared under the approach of ISO 9001: Quality Management System and NTE INEN 734: Wine elaboration. In conclusion, through the design of the standardization guide for the elaboration of wines based on fruit wastes, the commercial premises will benefit from a new product in the market that will allow them to have an economic income